A parietal memory network revealed by multiple MRI methods. Issue 9 (September 2015) - Gilmore, Adrian W.; Nelson, Steven M.; McDermott, Kathleen B.
Highlights We highlight a novel memory network, using evidence from multiple MRI methods. We term this network the parietal memory network (PMN). PMN regions deactivate to novel, but activate to familiar, stimuli. This network sits adjacent to, but is distinct from, the default mode network.